Electrical Heart Instability Evaluation in Conditions of Diastolic Heart Failure Suffered by Coronary Heart Disease Patients - Tatarchenko, E.P.; Pozdnyakova, N.V.; Morozova, O.E.; Petrushin, E.A. (IntechOpen, 2012)
None